The Effect of Reciprocal and Inclusion Teaching Styles on Volleyball Underhand Pass Learning Outcomes - Slamet Riyadi; Dewi Susilawati; Yudha M Saputra; Herdiansyah Herdiansyah (UNIB Press, 2023)
Thelack of learning to pass down is a problem that must be considered because if you are not skilled in passing down, most likely the goal of the volleyball game will not be achieved optimally and maximally. It is a challenge for the school and researchers to discover the factors that cause the lack of bottom-passing learning in the volleyball game. Based on the research hypothesis, this type of research is a quasi-experimental research consisting of two research groups: the group with the reciprocal learning model and the group with the inclusion learning model. This study aimed to obtain an overview of the improvement of volleyball bottom passing learning outcomes. In this study, the reciprocal learning model group (Group A) and the inclusion learning model group (Group B) Based on the results of hypothesis testing, the results were accepted or proven. The truth of the effects of hypothesis testing is also supported by research data using the t-test, which shows a calculated value greater than t-kritik (2.90 1.71). Thus, the hypothesis is accepted. It can be concluded that the average increase in mastery of learning with the reciprocal method is higher than the inclusion learning method. The reciprocal method significantly affects the learning outcomes of volleyball bottom passing. The inclusion method substantially affects the learning outcomes of volleyball bottom passing. There are differences in reciprocal methods and inclusion methods on volleyball bottom passing learning outcomes, and reciprocal methods are more effectively used in volleyball bottom passing learning games.